Analisis Strategi Pemasaran Sepeda Motor Listrik Menggunakan Metode Quantitative Strategic Planning Matrix (QSPM) - Wirawan, Denny; Isharyani, Muriani Emelda; Widada, Dharma (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
National electric motorcycle sales have increased significantly, yet U-Winfly Dua Putra Jaya E-Bike 2 Samarinda has experienced a decline. Based on data from Tirto.id and Liputan Finansial, sales in Indonesia rose from 11,532 units in 2023 to 63,146 units in 2024, an increase of 447%. However, U-Winfly has not achieved its target of 50 units per month. This study aims to identify internal and external factors influencing marketing strategies and to formulate alternative strategies to improve sales. Using the Quantitative Strategic Planning Matrix (QSPM), data were collected through observation, interviews, questionnaires, and documentation from 2023 to 2024. The analysis includes IFE, EFE, SWOT, SPACE, IE, Grand Strategy, and QSPM matrices. Results show IFE and EFE scores of 2.749 and 2.513, respectively. Priority strategies include strengthening social media marketing, developing energy-efficient products, and digitalizing operations to enhance U-Winfly’s market position.